Volume- and calcium-activated chloride channels in human umbilical vein endothelial cells - Zhong Ning; Fang Qi-Zhi; Zhang Yi; Zhou Zhao-Nian (Acta Pharmacologica Sinica, 2016)
"AIM: To characterize the properties of chloride currents and its modulation in human umbilical vein endothelial cells (HUVEC). METHODS: Using whole-cell patch-clamp recording techniques. RESULTS: Exposure of HUVEC to 13.5% and 27% hypotonic solution (HTS) induced a current ICl, vol. This current was correlated with the changes in cell volume and showed a modest outward rectification. It was slowly inactivated at positive potential (> 50 mV), and it was time- and voltage-independent in kinetics. The current densities (pA/pF) were 20 +/- 3 (13.5% HTS) and 58 +/- 4 (27% HTS, n = 7), respectively at +100 mV test potential. Applying GTP gamma s (300 mumol.L-1) elicited a current similar to ICl, vol, while cAMP (0.5 mmol.L-1) had no effect on the current. Increase in [Ca2+]i, either by directly loading cells with high concentration of Ca2+ (CaCl2), or by perfusing vasoactive agonist ATP (10 mumol.L-1), activated ICl, Ca. The current density was only (23 +/- 5) pA/pF (n = 8 cells). Such current was slowly activated at positive potential, inactivated quickly at negative potential, and showed strong outward rectification. Both currents were inhibited by DIDS and verapamil. Challenging a cell with elevated [Ca2+]i and HTS activated ICl, vol on the top of ICl, Ca in the same cell, suggested co-existence of these two currents and that they were modulated by different ways. cAMP-regulated chloride channel and ClC (chloride channel family) channel were absent. CONCLUSION: HUVEC express two kinds of chloride channels, ICl, vol activated by change in cell volume and ICl, Ca by elevation of [Ca2+]i, respectively."